Smoking cessation intervention among Vietnamese Americans: a controlled trial. (June 1995) - McPhee, Stephen J; Jenkins, Christopher NH; Wong, Ching; Fordham, Don; Lai, Ky Quoc; Bird, Joyce Adair; Moskowitz, Joel M
Abstract : Objective: To evaluate the effectiveness of a culturally appropriate, media-led information and education smoking cessation campaign. Design: Two-year controlled trial, multicomponent programme. Subjects and setting: Vietnamese men living in Santa Clara County, California, US. Main outcome measures: Pretest (1990) and post-test (1992) surveys of randomly selected Vietnamese men in Santa Clara County and Houston, Texas, serving as a comparison community. Results: In both 1990 and 1992, adult males in both communities were more likely to smoke if they were younger (p < 0.005), if they were more recent immigrants (p < 0.001), if they had less than a high school education (p < 0.005), or if their English proficiency was limited (p < 0.001). Between 1990 and 1992, smoking prevalence remained constant in Santa Clara County (36% in 1990; 36% in 1992), and in Houston (40% in 1990; 41% in 1992). The proportions of recent quitters, although greater in Santa Clara County than Houston, did not change significantly between pretest and post-test in either community. Conclusion: The continuing high smoking prevalence rate among Vietnamese men in Santa Clara County suggests a need for continuing intervention, particularly among recent immigrants.